Ethics in nursing: categorization of legal processes - Larissa Viana Ues; Leticia Helbingen Pereira; Rayssa Maria de Araújo Ferreira Paula Bastos; Luana Cássia Miranda Ribeiro; George Oliveira Silva; Katiane de Oliveira Campos; Ivete Santos Barreto (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to categorize factual elements of ethical-disciplinary nursing lawsuits in the state of Goiás. Methods: cross-sectional, retrospective study, based on secondary data obtained from ethical-disciplinary lawsuits filed at the Regional Nursing Council of Goiás (Coren-Goiás) between the years 2010 and 2019. Results: the highest number of lawsuits filed was in 2013 and 2014, with a greater frequency in the state capital. The majority came from the Nursing Ethics Committees and ex-officio complaints. The professional with most complaints was the nursing technician, aged between 31 and 40 years old, at the beginning of their career. The most common type of complaints referred to performing attributions that were not within the nursing competences. Conclusions: as a highlight are the contributions of this study to professional ethics in nursing and the clear need to consolidate these skills in nurses who are in training and in the continuous education for those already in the profession.